The Strategy of the Indonesian Maritime Security Agency in Conducting Maritime Security Patrols - Inshan Padillah; Lukman Yudho P; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Historically, the Djuanda Declaration has been a significant achievement in Indonesia's maritime diplomacy, securing the territorial waters and sovereignty of the Unitary State of the Republic of Indonesia. The Geneva Conventions and participation in the International Maritime Organization require a country to ensure safety and security within its waters, a task assigned to the Indonesian Maritime Security Agency (Bakamla RI), which evolved from the Indonesian Maritime Security Coordination Agency (Bakorkamla) as Indonesia's Coast Guard. The complex security threats and the vast maritime territory of Indonesia present significant challenges. A maritime security strategy is expected to minimize and address these issues. This research employs a qualitative descriptive method. The results indicate that many cases occurred in 2023 based on official reports from the Indonesian Maritime Security Agency. According to the strategy theory of means, ways, and ends, two conclusions can be drawn regarding internal institutional strengthening: First, improving the understanding and application of Indonesia's maritime geopolitics. Second, reorganizing maritime security and law enforcement agencies based on Pancasila values. Furthermore, collaboration among cooperating parties can yield three levels of communication. For external institutional strengthening, maritime diplomacy can be pursued to maintain cooperative relationships and training with international Coast Guards.